Developing a Conceptual Framework of Instructional Model for Creating an Innovative Business Project: Applying the Sufficiency Economy Philosophy for Private Vocational Colleges in Bangkok, Thailand - Budhtranon, Wanyada; Chianchana, Chaiwichit; Kamkhuntod, Sayam (Journal of Technical Education and Training, 2021)
Vocational students in business programs become the future of the global workforce; this field requires innovation, given its added value. Importantly, the balance among profit, people, and the planet is greatly needed. Adaptability to sudden changes, such as pandemics or economic crises, is essential. This research developed a conceptual framework of instructional model for creating innovative projects applying the sufficiency economy philosophy (SEP), which aims to balance prosperity, society, environment, and culture with risk management for private vocational colleges in Bangkok, Thailand. The conceptual framework of instructional model was created from a literature review and empirical studies. Empirical data was gathered by studying current business project instructions from stratified random samples given by 250 teachers. The findings showed that instruction of basic business management, entrepreneurship, risk management, business innovation, and social responsibility are separate instead of integrated and applied to real situations. Furthermore, student business innovation in projects is low, while the suggestions to apply the SEP to business project instruction are high. The conceptual framework of instructional model consisted of instructions and assessments, based on design thinking, SEP, constructivist learning theory, and project-based learning. These instructions and assessments led to student learning outcomes that include the knowledge, skills, and attributes necessary to develop socially responsible, risk-manageable, and innovative business projects. Evaluation of the conceptual framework of instructional model’s feasibility by five experts resulted in high or very high ratings of all items.